2012
DOI: 10.1038/jhh.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the renin–angiotensin–aldosterone system is associated with cardiovascular risk factors and early mortality in established coronary heart disease

Abstract: This study examined renin-angiotensin-aldosterone (RAAS) system gene variants for associations with cardiovascular risk factors and outcomes in coronary heart disease. Coronary disease patients (n ¼ 1186) were genotyped for 21 single-nucleotide polymorphisms (SNPs) within angiotensinogen (AGT), angiotensin-converting enzyme (ACE), angiotensin-II type-1 receptor (AGTR1) and aldosterone synthase (CYP11B2). Associations with all-cause mortality and cardiovascular readmissions were assessed over a median of 3.0 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
(44 reference statements)
0
13
0
3
Order By: Relevance
“…The RAS has been the target of active research interest since the discovery of renin more than 100 years ago (Tigerstedt R & PG., 1898), reflecting its importance in the pathogenesis of hypertension and other cardiovascular diseases (Ellis, et al, 2012; Hsueh & Wyne, 2011; Re, 2004; Te Riet, van Esch, Roks, van den Meiracker, & Danser, 2015; Vijayaraghavan & Deedwania, 2011). In the traditional view of the systemic RAS, active renin is generated by the removal of a prosegment from prorenin, a precursor of renin, in the juxtaglomerular cells of the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The RAS has been the target of active research interest since the discovery of renin more than 100 years ago (Tigerstedt R & PG., 1898), reflecting its importance in the pathogenesis of hypertension and other cardiovascular diseases (Ellis, et al, 2012; Hsueh & Wyne, 2011; Re, 2004; Te Riet, van Esch, Roks, van den Meiracker, & Danser, 2015; Vijayaraghavan & Deedwania, 2011). In the traditional view of the systemic RAS, active renin is generated by the removal of a prosegment from prorenin, a precursor of renin, in the juxtaglomerular cells of the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found a significant association of the minor allele of rs11122576 with CHD mortality in a cohort of 1186 CHD participants mostly of European ancestry-after 3-years of follow-up. The minor allele of rs1122576 was also associated with of higher risk of renal disease, type 2 diabetes, and higher body mass index in that study (Ellis et al, 2013). Similarly to the CHD results, there were more marginally significant associations among African Americans compared to Caucasians for the HF outcome, however none were close to statistical significance.…”
Section: Discussionmentioning
confidence: 74%
“…Связь 235Тhr поли-морфизма гена AGT с неблагоприятным исходом ИМ в молодом возрасте отмечена в работах Elis KL, et al [5], Hara M, et al [6].…”
Section: материал и методыunclassified
“…В дополнение к этому Hara M, et al, наблюдая на протяжении 5 лет за пациентами, перенесшими ИМ (n=3149), пришли к выводу, что лица с Т235Т мутантным гомозигот-ным генотипом имеют более низкий процент выжи-ваемости в сравнении с нормальным М235М гено-типом. Подтверждением ассоциации 235Т полимор-физма и Т235Т генотипа гена AGT с АГ в детском возрасте являются экспериментальные данные, полученные автором [7] в лонгитюдном исследова-нии на протяжении 35 лет (1977-2012) с участием 507 человек [5][6][7]. примечания: p -достоверность различий для контроля и больных ССЗ (р1), спортсменов и больных ССЗ (p2), контроля и спортсменов (p3), OR1 -относитель-ный риск (для генотипов), OR2 -относительный риск (для аллелей).…”
Section: материал и методыunclassified
See 1 more Smart Citation